Geothermal power plants principles, applications, case studies, and environmental impact - DiPippo, Ronald (Butterworth-Heinemann, 2012)
Now in its 3rd edition, this single resource covers all aspects of the utilization of geothermal energy for power generation using fundamental scientific and engineering principles. Its practical emphasis is enhanced by the use of case studies from real plants that increase the reader's understanding of geothermal energy conversion and provide a unique compilation of hard-to-obtain data and experience. Important new chapters cover Hot Dry Rock, Enhanced Geothermal Systems, and Deep Hydrothermal Systems. New, international case studies provide practical, hands-on knowledge. Provides coverage of all aspects of the utilization of geothermal energy for power generation from fundamental scientific and engineering principlesInternational case studies from real plants provide a unique compilation of hard-to-obtain data and experienceIncludes pivotal updates on advances in Hot Dry Rock, Enhanced Geothermal Systems, and Deep Hydrothermal Systems.
Keywords: Geothermal power plants.; Geothermal resources.; Geothermal engineering.; elektronické knihy; electronic books